SOSIALISASI DAN PELATIHAN TABULAMPOT (TANAMAN BUAH DALAM POT) YANG DILAKSANAKAN DI PERUMAHAN GREEN PANONGAN RESIDENCE TANGERANG - Arfan; Agistiawati, Eva; Mariyanah, Siti; Rahmawati, Yunita; Kurniawan, Muhammad Arif; Fuadi, Aris; Wahid, Abdul (Jurnal Abdimas Universitas Insan Pembangunan Indonesia, 2026)
This community service (PKM) program aims to empower the residents of Green Residence Panongan, Tangerang, through the cultivation of fruit trees in pots, locally known as Tabulampot. The initiative was driven by the challenges of limited green open space and the need for improved family food security within urban housing environments. The program employed a Community-Based Development (CBD) approach and participatory andragogy methods, which included socialization, technical demonstrations, guided practice, and intensive mentoring conducted from September 2025 to February 2026. The results indicated a significant success in achieving the program's objectives. Participants' cognitive knowledge regarding urban farming increased by 68%, and 100% of the 35 participating families successfully demonstrated the technical skills required for planting. The adoption rate reached 82%, surpassing the initial target of 75%, with a plant survival rate of 89% after three months. Furthermore, the program successfully established the "Green Residence Tabulampot Community," complete with an organizational structure and a digital communication platform to ensure long-term sustainability. This initiative not only enhances environmental greening but also provides potential economic savings of approximately Rp 100,000 to Rp 300,000 per month per household and promotes a healthier lifestyle through the production of fresh, organic fruit in limited residential spaces.